1994
DOI: 10.1002/j.1460-2075.1994.tb06329.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin acts in synergy with PMA to inactivate I kappa B/MAD3, an inhibitor of NF-kappa B.

Abstract: The interleukin-2 (IL-2) promoter consists of several independent T cell receptor (TcR) responsive elements. The induction of promoters dependent on these elements is inhibitable by the immunosuppressants cyclosporin A (CsA) and tacrolimus . Calcineurin, a Ca2+/calmodulin-dependent protein phosphatase, is the FK-506-and CsA-sensitive enzyme required for TcR mediated activation of the LL-2 promoter. We report that a constitutively active form of calcineurin partially substitutes for the Ca2+ co-stimulus require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
229
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(241 citation statements)
references
References 68 publications
10
229
2
Order By: Relevance
“…Calcineurin is a Ca 2+ /calmodulindependent protein phosphatase involved in various signalling pathways of vesicular trafficking [42]. Notably, inhibitors of calcineurin counteracted the stimulatory effect of inositol hexakisphosphate on endocytosis in insulin-producing cells [43], suggesting that calcineurin might act as a modulator of the endocytotic process in the beta cell.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin is a Ca 2+ /calmodulindependent protein phosphatase involved in various signalling pathways of vesicular trafficking [42]. Notably, inhibitors of calcineurin counteracted the stimulatory effect of inositol hexakisphosphate on endocytosis in insulin-producing cells [43], suggesting that calcineurin might act as a modulator of the endocytotic process in the beta cell.…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin is a Ca2+/ calmodulin-regulated protein phosphatase with broad substrate specificity. Calcineurin substrates that could affect neuronal survival include NOS [22], transcription factors [27,28] and the NMDA receptor itself [29][30][31][32][33]. In this system, the lack of a protective effect of NC-nitro-L-arginine rules out the involvement of endogenous NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A (CsA), inhibits B-and T-cell proliferation by blocking the activity of calcineurin, a calcium and calmodulin-dependent serine/threonine phosphatase (Frantz et al, 1994). Several reports have shown that CsA can also inhibit NF-kB induction, although the mechanism by which CsA exerts this inhibitory effect may differ in different situations.…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%
“…Some inhibit NF-kB nuclear translocation by stabilizing IkBa (Meyer et al, 1997), some may act on NF-kB through inhibiting calcineurin (Frantz et al, 1994), some by binding heatshock proteins (Tepper et al, 1995) and some by modulating the DNA binding or transactivation potential of NF-kB (McCaffrey et al, 1994;Wechsler et al, 1994;Kunz et al, 1995;Qiu et al, 1999).…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%